Scoping review of the applications of peptide microarrays on the fight against human infections - Arthur Vengesai; Maritha Kasambala; Hamlet Mutandadzi; Tariro L Mduluza-Jokonya; Takafira Mduluza; Thajasvarie Naicker (Public Library of Science, 2023)
Introduction: This scoping review explores the use of peptide microarrays in the fight against infectious diseases. The research domains explored included the use of peptide microarrays in the mapping of linear B-cell and T cell epitopes, antimicrobial peptide discovery, immunosignature characterisation and disease immunodiagnostics. This review also provides a short overview of peptide microarray synthesis.